Theoretic Analysis of Implicatures in Pride and Prejudice and Its Pedagogical Implications - Dita Rizki Anggraini; Ismail Petrus; Rita Inderawati (Script Journal: Journal of Linguistics and English Teaching, 2019)
This study was aimed at finding out the implicatures, the types of the implicatures, and the intended meaning of the implicatures employed by the characters in Jane Austen’s Pride and Prejudice. This study was a descriptive qualitative study with corpus-based approach. The data were collected through some procedures, namely reading the novel repeatedly and thoroughly, determining the utterances containing implicatures in dialogues based on the relevance theory, and selecting and organizing the data to be analyzed. To analyze the data, the procedures were presenting and describing the data, interpreting the data by referring to the relevance theory, determining the implicated premises and implicated conclusions, determining the strongly implicated conclusions and weakly implicated conclusions, and interpreting and describing the intended meanings of the implicatures. From the results, there were 60 implicatures found in the novel and the two types of them were strong and weak implicatures. As the follow-up, a dissemination to the second semester students of Graduate Program of Sriwijaya University was conducted which yielded to the result that there was no significant association between the respondents’ knowledge of implicatures and relevance theory and their performance in analyzing implicatures using the theory with the p-value of 0.406 (p-value > 0.05).